2005
DOI: 10.1007/bf03217417
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes to mathematics and performance in limits of functions

Abstract: The main aim of this article is to discuss the attitudes to mathematics of students taking a basic mathematics course at a Swedish university, and to explore possible links between how well such students manage to solve tasks about limits of functions and their attitudes. Two groups, each of about a hundred students, were investigated using questionnaires, field notes and interviews. From the results presented a connection can be inferred between students' attitudes to mathematics and their ability to solve li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
2
14
0
5
Order By: Relevance
“…Some limit-knowledge studies (Barak, 2007;Baştürk & Dönmez 2011;Denbel, 2014;Juter, 2006;Szydlik, 2000;Tangül et al, 2015) revealed students' difficulties and misconceptions. In the studies by Barak (2007) and Baştürk and Dönmez (2011), students were determined to have different misconceptions about limit knowledge.…”
Section: Difficulties In Learning and Teaching Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some limit-knowledge studies (Barak, 2007;Baştürk & Dönmez 2011;Denbel, 2014;Juter, 2006;Szydlik, 2000;Tangül et al, 2015) revealed students' difficulties and misconceptions. In the studies by Barak (2007) and Baştürk and Dönmez (2011), students were determined to have different misconceptions about limit knowledge.…”
Section: Difficulties In Learning and Teaching Limitsmentioning
confidence: 99%
“…Also, Denbel declared that students have many misconceptions, such as limits representing the value of a function at a point, a limit can be found though a method of substitution, or that one divided by zero equals zero. Juter (2006) reported that students have many different cognitive difficulties related to limit knowledge, such as infinite series and how functions never reach their limits. Szydlik (2000) declared that limit beliefs and understanding are highly related to one another.…”
Section: Difficulties In Learning and Teaching Limitsmentioning
confidence: 99%
“…They may differ from situation to situation, and often for (at first sight) incomprehensible reasons. What these affective aspects have in common is that they influence achievement (Juter, 2005;Kloosterman, 1988;Ma & Kishor, 1997) via metacognition or social aspects (among others).…”
Section: Affective Aspectsmentioning
confidence: 99%
“…Winheller, Hattie ir Brown (2013) teigia, kad suvokiama mokymosi dalyko mokymo kokybė formuoja nuostatą dėl matematikos, o geresni santykiai su bendraklasiais ir stipresnis įsitraukimas į šiuos santykius netgi siejamas su labiau neigiamu nusistatymu dėl matematikos mokymosi, blogesniu matematinių užduočių atlikimu ir prastesniais akademiniais pasiekimais. Atlikti tyrimai rodo, kad nuostata dėl matematikos nulemia matematinių uždavinių sprendimo kokybę, akademinius pasiekimus ir yra susijusi su saviveiksmingumo įvertinimu, o neigiama matematikos mokymosi nuostata yra siejama su žemais akademiniais pasiekimais, tačiau lieka neaišku, ar tokie akademiniai pasiekimai sukelia nuostatą dėl matematikos ar yra neigiamos matematikos mokymosi nuostatos rezultatas (Nicolaidou & Philippou, 2003;Juter, 2005;Hemmings, Grootenboer & Kay, 2010).…”
Section: Raminta Seniūnaitėunclassified
“…Tyrimo rezultatai rodo, kad metakognityvių įgūdžių lavinimas turi teigiamą poveikį nuostatai dėl matematikos ir akademiniams pasiekimams. Yuksel (2013) tyrimo duomenimis, pažinimo reguliavimas ir žinios apie pažinimą leidžia prognozuoti nuostatas dėl matematikos ir akademinius pasiekimus (Yuksel, 2013) ir šie tyrimo rezultatai oponuoja kitų ty-rėjų (Sperling, et al, 2002;Countinho & Neuman, 2008;Kleitman & Gibson, 2011;Jagals & van der Walt, 2013;Nicolaidou et al, 2003;Juter, 2005;Hemmings et al, 2011) gautiems rezultatams, kad metakognityvus sąmoningumas tiesiogiai neturi įtakos akademiniams pasiekimams. Sahin, Kendir (2013), Kleitman ir Gibson (2011) įrodė, kad mokiniai, apmokyti naudotis metakognityviomis strategijomis, turėjo aukštesnę nuostatą dėl matematikos, tai nulėmė labiau teigiamos nuostatos dėl matematikos atsiradimą ir geresnius akademinius pasiekimus.…”
Section: Raminta Seniūnaitėunclassified